Effect Stress and Vibration Analysis at NACA Airfoil towards Axial Fan Blade Performance - Eky Novianarenti; Muhammad Anis Mustaghfirin; Achmad Fardiansyah Abdillah (Journal of Mechanical Engineering, Science, and Innovation, 2022)
Axial fans are widely applied in the industrial sector. Axial fans are used for ventilation systems and other cooling systems. The blade design of the axial fan requires an airfoil study. Unfortunately, there are not many articles that discuss in detail about airfoils, especially on noise and vibration that can have an impact on axial fan performance using computational fluid methods or software. This study performs axial fan analysis using computational methods with ANSYS Fluent, Static Structural, Modal and Harmonic Response software to obtain the values of stress, vibration and fluid flow. The experimental design used is using NACA 1412, 4142, and 6412 airfoils on the tip with variations in angles of 60, 74, and 80. While on the hub uses NACA 9312, 9412, and 9512 airfoils with angle variations of 20, 30, and 60 and simulated to find the value of vibration and stress analysis. The 3D axial fan design is imported into the ANSYS Fluent, Static Structural, Modal and Harmonic Response software. The simulation results using Ansys Fluent, shows the pressure contour with a maximum value of 198.424 Pa and Velocity streamline with a maximum value of 28.8669 m/s. the results of the Ansys Static Structural simulation show that the average total deformation is 9.9275e-008 m. The simulation results using Ansys Modal, show that there is a natural frequency of 287.8 Hz and the simulation results of Ansys Harmonic Response obtained an average total deformation of 5.0809e-012 m and the equivalent stress value with a maximum value of σ y, max = 0.20186 Pa.